Preoperative glenoid considerations for shoulder arthroplasty: a review. Issue 3 (2nd March 2020) - Gates, Stephen; Sager, Brain; Khazzam, Michael
Abstract : Preoperative assessment of the glenoid in the setting of shoulder arthroplasty is critical to account for variations in glenoid morphology, wear, version, inclination, and glenohumeral subluxation. Three-dimensional computed tomography (3D CT) scan assessment of the morphology of glenoid erosion allows for a more accurate surgical decision-making process to correct deformity and restore the joint line. Newer technology has brought forth computer-assisted software for glenoid planning in shoulder arthroplasty and patient-specific instrumentation. There have been promising early findings, although further evaluation is needed to determine how this technology impacts implant survivorship, function, and patient-reported outcomes. Cite this article: EFORT Open Rev 2020;5:126-137. DOI: 10.1302/2058-5241.5.190011